Class II Phosphoinositide 3-Kinases Contribute to Endothelial Cells Morphogenesis - Tibolla, G.; Piñeiro, R.; Chiozzotto, D.; Mavrommati, I.; Wheeler, A.; Norata, G.; Catapano, A.; Maffucci, T.; Falasca, Marco (2013)
The question of whether the distinct isoforms of the family of enzymes phosphoinositide 3-kinases (PI3Ks) play redundant roles within a cell or whether they control distinct cellular processes or distinct steps within the same cellular process has gained considerable importance in the recent years due to the development of inhibitors able to selectively target individual isoforms. It is important to understand whether inhibition of one PI3K can result in compensatory effect from other isoform(s) and therefore whether strategies aimed at simultaneously blocking more than one PI3K may be needed. In this study we investigated the relative contribution of distinct PI3K isoforms to endothelial cells (EC) functions specifically regulated by the sphingolipid sphingosine-1-phosphate (S1P) and by high density lipoproteins (HDL), the major carrier of S1P in human plasma. Here we show that a co-ordinated action of different PI3Ks is required to tightly regulate remodelling of EC on Matrigel, a process dependent on cell proliferation, apoptosis and migration. The contribution of each isoform to this process appears to be distinct, with the class II enzyme PI3K-C2β and the class IB isoform p110γ mainly regulating the S1P- and HDL-dependent EC migration and PI3K-C2α primarily controlling EC survival. Data further indicate that PI3K-C2β and p110γ control distinct steps involved in cell migration supporting the hypothesis that different PI3Ks regulate distinct cellular processes.